Efficacy of Prophylactic Two Different Doses of Intravenous Ondansetron in the Prevention of Spinal Anesthesia Induced Hypotension and Bradycardia in Elective Cesarean Section - M. Saeed, Dr. Zainab M. Jaafar; Mahboba, Dr. Jaafar Hameed; Rukhis, Dr. Ahmed Mohammed (Journal of Science in Medicine and Life, 2024)
Background: The most widely used regional anesthetic approach for cesarean sections is spinal anesthesia. On the other hand, hypotension and bradycardia are the most frequent side effects it is frequently seen in cases of profound circulatory collapse during neuraxial anesthesia. Researchers began investigating how ondansetron might lessen these subsequences. Aim of the study: To evaluate the effects of two different doses of IV ondansetron on spinal anesthesia induced hypotension and bradycardia in elective cesarean section. Patients and method: A single blind prospective randomized control trial was conducted in Al_Zahraa Teaching Hospital by enrolling 90 patients using a random sample technique. Patients were allocated into ondansetron groups (150 mcg/kg as C), (75 mcg/kg as B) and (placebo as A). Demographic data, hemodynamic parameters, and the incidence of hypotension and bradycardia. Result: A considerable decrease in hemodynamic variables was observed in group A as compared with ondansetron groups within 30 minute time intervals (p value ˂0.05, the significance was more obvious in group C as compared with group B. The requests for vasopressor agents and atropine were more in group A versus ondansetron groups with a p value less than 0.001. Conclusion: both two groups of ondansetron manifest a decrease in the incidence of hypotension and use of vasopressor or atropine but group C was exceedingly effective in the decline of hypotension after spinal anesthesia in elective cesarean section.